圖書館智慧服務: 基於知識挖掘與推薦系統的模式研究: Research of Library's Smart Service, Derived from Recommender Systems and Knowledge Discoveries - Quan, 刘燕权 Liu Yan; Yingchun, 王颖纯 Wang (Nook Digital LLC by Barnes & Noble®, 2022)
本書內容包括：智慧圖書館、知識服務、移動服務、推薦系統、無線射頻技術、學科及學術資源服務等關於中國與美國信息技術、知識管理和學科拓展。 本書可作為大中專信息管理學院、圖書館學院、軟件學院、管理學院，及所有相關專業的本科生、碩士生、博士生和教師等的專業教材或教學參考書。亦可作為計算機、圖書情報、信息管理，網絡文化教育等領域的研究人員和工程技術人員、管理人員、服務人員的信息參考資料。作為大學圖書館，公共圖書館，專業圖書館，各類信息中心，IT與網絡公司等機構收藏本圖書，為開展智慧服務提供借鑒參考。本書也可為信息資源管理相關行政部門實際工作提供政策建議，為大眾提供各類知識閱讀。
Keywords: dept.ils

Contactless Services: A Survey of the Practices of Large Public Libraries in China - Guo, Y.; Yang, Z.; Yuan, Y.; Ma, H.; Liu, Y.Q. (Information Technology and Libraries, 2022)
Contactless services have become a common way for public libraries to provide services. As a result, the strategy used by public libraries in China will effectively stop the spread of epidemics caused by human touch and will serve as a model for other libraries throughout the world. The primary goal of this study is to gain a deeper understanding of the contactless service measures provided by large Chinese public libraries for users in the pandemic era, as well as the challenges and countermeasures for providing such services. The data for this study was obtained using a combination of website investigation, content analysis, and telephone interviews for an analytical survey study of 128 large public libraries in China. The study finds that touch-free information dissemination, remote resources use, no-touch interaction self-services, network services, online reference, and smart services without personal interactions are among the contactless services available in Chinese public libraries. Exploring the current state of contactless services in large public libraries in China will help to fill a need for empirical attention to contactless services in libraries and the public sector. Up-to-date information to assist libraries all over the world in improving their contactless services implementation and practices is provided. © 2022.
Keywords: dept.ils; peer-reviewed